The macroeconomics of price adjustments under information frictions and menu costs - Nunes, Vivian Malta (2013)
This thesis studies price-setting models and analyzes their macroeconomic im- plications. In the rst two chapters I study general models in which rms pricing decisions are a¤ected by menu costs and information costs. In Chapter 1 I estimate these models using American data on price changes, concluding that: information costs are signi cantly higher than menu costs; real data does not t into the model in which rms receive information about aggregate conditions freely but pay for idio- syncratic information. In Chapter 2 I explore the consequences of monetary shocks and disin ation announcements using the previously estimated models. I show that the degree of monetary non-neutrality is larger in an economy where part of the infor- mation is given for free. Chapter 3 is a coauthored paper with Carlos Carvalho and Antonella Tutino. We abstract from menu costs and examine a price-setting model in which rms are subject to a Shannon constraint on information ow. We calibrate the model and investigate impulse response functions to aggregate and idiosyncratic shocks. We nd that, rather than tracking aggregate and idiosyncratic conditions independently, rms prefer to process information altogether, and that leads to a faster overall price level adjustment, and thus to less real e¤ects persistence after a monetary shock.